Extruded instant millet thick porridge (tuwo) flour and market testing in Niger - Moustapha Moussa; Antonio J. Vela; Amudhan Ponrajan; Osvaldo H. Campanella; Martin R. Okos; Nilupa S. Gunaratna; Mario G. Ferruzzi; Bruce R. Hamaker (Applied Food Research)
Tuwo is a thick millet (or sorghum) porridge staple food in Niger and the western Sahel (under different names) that is consumed freshly prepared, but the preparation is time-consuming. Growing urban populations in Africa require ready-to-use food products as an alternative to time-consuming traditional products. In the present study, a process was developed to produce instant tuwo flour using a low-cost single-screw extruder. Millet grain was decorticated and ground, moisture equilibrated to 35%, extruded to expanded rods, dried, and rods ground to flour. The instant tuwo flour only requires hydration in boiling or hot water. The instant tuwo showed a similar shear-thinning behavior as the traditional tuwo, with lower K (15.95 Pa∙s) and higher n (0.39) values, which led to similar tan(δ)1 values for both samples (0.229 and 0.225). Results from a Home-Use Test showed that potential consumers in various districts of Niamey ranked positively the ease of preparation and the organoleptic characteristics of the instant tuwo. A 10-week market sales study showed good acceptability by the urban population in Niamey with comparatively high and consistent sales, totaling ∼700 kg. Compared to other traditional cereal-based processed goods, the instant tuwo product was among the 4 highest sold products. This study shows the commercial potential of a convenient instant porridge product that could expand the millet market in Niger and surrounding region. It also indicates that Sahelian urban consumers are open to new convenient alternatives to the traditional food when they meet the expected quality parameters.